PENINGKATAN KREATIVITAS IBU-IBU PKK MUDA SETIA MELALUI PEMBUATAN SABUN CUCI PIRING EKONOMIS - Dedi Irawan; Atika Chairinnisa; Desyanifransisca Giawa; Fajar Rahmat Prayogi; Farida Ayuningsi Simanullang; Lidia Dewi Marlina Pardede; Lydia Damayanti; Mega Betrinadyan; Muhammad Zidane Nugraha; Selvi Rotua Simamora; Yana Sartika (Nusantara Hasana Journal, 2022)
Dishwashing soap is one of the household items that must be in every home because of its use in cleaning up dirt on cooking utensils. Every household spends a lot of money to buy soap for washing dishes, meanwhile dishwashing soap can be made at home with ingredients that are easy to get and economical value. The lack of public knowledge about the ingredients and methods of making dish soap in Muda Setia Village causes people to spend more money to buy dish soap. Therefore, KUKERTA students at the University of Riau empower the community in Muda Setia Village, especially PKK women in making dish soap. The method used by Kukerta students is by delivering materials and direct demonstrations in front of PKK women. The location selection method is carried out in a purposive manner through considerations that are in accordance with the purpose of service. The purpose of this activity is to provide socialization, empowerment and training to PKK women, most of whom work as housewives and farm laborers in oil palm plantations. Through this empowerment, they succeeded in developing the abilities of women in the village of Muda Setia as well as providing opportunities to open a business by making dishwashing soap that has economic value.